Identification of genes related to drought tolerance in 41 varieties of quinoa (Chenopodium quinoa Willd) - Serna, F. (2020)
The objective of the research was to identify the genes related to drought tolerance in quinoa. For this, 41 varieties of Chenopodium quinoa Willd were evaluated with six repetitions; in the flowering stage, three pots/material, of each variety, were randomly selected to be induced to total drought for two weeks, resuming irrigation after that period, the other three were the control. From day 27 after sowing, the chlorophyll level was measured and classified as tolerant or susceptible to drought, based on its chlorophyll content index (CCI). For the identification of genes, leaf samples of three varieties were taken (Red head, Salcedo INIA and Kankolla 1). RNA Extraction was performed using reagent® TRI reagent and for the transcriptome sequencing the Ilumina platform was used. 26 genes were identified in the three varieties of quinoa, but in the drought tolerant varieties; three of them are regulated upwards when exposed to drought and five genes (AUR62037809, AUR62000271, AUR62037807, AUR62042825 AUR62009791) have a change in their pattern of expression as a result of drought exposure.